Making unemployment insurance work: Reforming unemployment insurance ; toward greater employment - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1996)
What is needed to solve the problem of growing long-term unemployment is a two-tiered system that distinguishes between short-term and long-term unemployment. The system should continue to function as an insurance program for 26 weeks to allow workers to search for employment that represents the best match with their experience, skills, and credentials. The first tier of the improved system would include reforms to reduce short-term employment through such means as altering the employer taxes that finance unemployment insurance and instituting work-sharing arrangements in order to reduce the incidence of layoffs and to maintain employment levels during periods of economic decline. The second tier would include services such as reemployment assessment and workshops and training programs to help unemployed workers find work that matches their skills or help them acquire new skills that would make them more marketable. Unemployment insurance benefits beyond 26 weeks would be contingent upon workers' making use of these services. Levin-Waldman states that the goal of reform is not merely to achieve greater efficiency in facilitating reemployment, but to enhance a core value of American society: work.
Keywords: 330